(untitled) (Fiep Bulletin - online, 2014)
This text, presented as a theoretical essay, approaches ways to build the social identity of young people who live in a society where there are virtualizations of the body. It is important to note that there is an evolution of the concepts of how to use science as a way to interpret this new paradigm between the subject and his/her will to make his/her dreams come true. The aspect of the subject’s body identity has become ephemeral and superficial. The risks to reach beauty and find the ways to build the archetype of happiness are not taken into account any longer. The individual finds resistance to build his/her authentic body. Thus, not rarely do we find cases of eating disorders among teenagers.